2004
DOI: 10.1177/153537020422900711
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Metastatic and Nonmetastatic Breast Tumors in Old Mice

Abstract: Breast cancer incidence and mortality increase with age. A better understanding of the biological behavior of metastatic and nonmetastatic breast tumors in older subjects may help to develop improved breast cancer therapies. In this study, we used syngeneic metastatic (4TO7cg) and nonmetastatic (64pT) mouse breast tumor models at three age levels to evaluate various characteristics that are considered to be important for effective anti-breast cancer immunotherapy. These included tumor size and growth, metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…In a previous study, we showed that Mage-b is highly expressed in 4TO7cg metastases and tumours in young and old mice (Gravekamp et al, 2004). We have also shown that Mage-b is highly expressed in 4T1 metastases and tumours of young mice .…”
Section: Expression Of Mage-b In Metastases and Tumours At Old Agementioning
confidence: 98%
See 2 more Smart Citations
“…In a previous study, we showed that Mage-b is highly expressed in 4TO7cg metastases and tumours in young and old mice (Gravekamp et al, 2004). We have also shown that Mage-b is highly expressed in 4T1 metastases and tumours of young mice .…”
Section: Expression Of Mage-b In Metastases and Tumours At Old Agementioning
confidence: 98%
“…These spontaneous tumours also express Mage-b (unpublished results). Age-related effects on the growth of 4TO7cg tumours and metastases have also been extensively analysed in a previous study (Gravekamp et al, 2004). In contrast to 4TO7cg, a dramatic effect of ageing was observed in the 4T1 model.…”
Section: Expression Of Mage-b In Metastases and Tumours At Old Agementioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the generation of immune responses against all other TAA than Mage-b, we used 64pT instead 4T1 tumour cells in the restimulation assay. 64pT is a syngeneic breast tumour cell, highly expressing Mage-b (Gravekamp et al, 2004) and highly secreting IL-6 (3000 pg ml À1 ) (Gravekamp et al, 2008). Indeed, addition of anti-IL-6 antibodies to the in vitro restimulation assay significantly increased the production of IFNg, whereas the production of IFNg could not be induced in the same restimulation assay without anti-IL-6 antibodies ( Figure 6A).…”
Section: The Effect Of Il-6 On Mage-b-specific Immune Responses In Vitromentioning
confidence: 98%
“…Two days later, the number of IFNg-producing cells was determined by ELISPOT reader as described above. In addition, anti-IL-6 antibodies (50 mg ml À1 ) were either or not added to the wells with LNs (2 Â 10 5 ) and syngeneic 64pT tumour cells (1 Â 10 4 ; treated with mitomycin C; expressing highly Mage-b; Gravekamp et al, 2004), and secreting highly IL-6 (3000 pg ml À1 ) (Gravekamp et al, 2008), in 200 ml of RPMI containing 10% FBS. Two days later, the production of IFNg was determined by quantitative ELISA as described previously (Sypniewska et al, 2005).…”
Section: The Effect Of Il-6 On Mage-b-specific Immune Responsesmentioning
confidence: 99%